Religiosity as Moderation of Academic Cheating of Accounting Students with the Hexagon Theory Approach - Istiqama Asviola; Sultan; Sahrir (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the influence of aspects of Hexagon Theory consisting of pressure, opportunity, rationalization, ability, arrogance, and collusion as well as aspects of religiosity as moderation variables on academic cheating. The primary data used in this study was collected by distributing questionnaires to students majoring in accounting, faculty of Economics and Business at the University of Muhammadiyah Palopo, Class of 2020. The sampling method with the simple random sampling method by calculating a minimum sample using the slovin formula and obtained 68 samples. The collected data was analyzed using WarpPLS 7.0 software. The test results found that pressure, rationalization, ability and collusion did not have a positive and significant effect on academic cheating while opportunity and ability had a positive and significant effect on academic cheating. Higher religiosity can minimize rationality and arrogance towards academic cheating. But religiosity can strengthen collusion to commit academic cheating. High religiosity cannot hinder academic cheating which is influenced by pressure, opportunity, and ability which are supporting factors for academic cheating